Biogenic synthesis of silver palladium bimetallic nanoparticles from fruit extract of Terminalia chebula – In vitro evaluation of anticancer and antimicrobial activity - Bhagavathi Sundaram Sivamaruthi (2019)
© 2019 Elsevier B.V. Biogenic synthesis of nanoparticles used for biomedical application has received much attention nowadays owing to its quick synthesis, cost effectiveness and biocompatible nature. The present study focuses on the biosynthesis of silver palladium bimetallic nanoparticles (AgPd NPs) from aqueous fruit extract of Terminalia chebula. Synthesized AgPd NP was assessed for antimicrobial activity and anticancer potential against lung cancer cells (A549). XRD analysis confirmed the formation of face centered cubic crystalline structure with average size of 20 nm, which was affirmed by DLS analysis. Uniform spherical shaped nanoparticles were observed in SEM and TEM analysis. Zeta potential value of −14.4 mV illustrated the stability of AgPd NPs. Anticancer studies illustrated that AgPd NPs induced ROS generation in lung cancer cells, thereby stimulating mitochondrial apoptotic pathway causing cell death. AgPd NPs exhibited antimicrobial activity against methicillin resistant Staphylococcus aureus and Pseudomonas aeruginosa. In vitro toxicity studies revealed that AgPd NPs exhibited no cyototoxic and hemolytic effect upto its maximum dose (200 μg/ml), ensuring the biocompatibility of nanoparticles. Our findings demonstrated that aqueous extract of T. chebula act as effective reducing and stabilizing agent for green synthesis of biocompatible AgPd NPs, which exhibits potent antimicrobial and anticancer activities.